Assistance of Sustainable Forest Management through Strengthening of Human and Social Capital in Arjuna Mount East Java Community - Matheus Nugroho; Hermanto, Yustinus Budi; Obaid, Hind Hussein; Kasheem, Majdy (LPPM Universitas Yudharta Pasuruan, 2024)
This study is part of a community service project aimed at examining the role of human and social capital in the sustainable forest management of Mount Arjuna East Java. The objective of the community service initiative is to empower local communities around the forest to actively participate in forest conservation efforts. The study employs a descriptive method with a survey technique to gather factual data from the research area, which includes the spring areas around Mount Arjuna in East Java, Indonesia. The study population consists of communities from three villages: Leduk, Jatiarjo, and Dayurejo, located in Pasuruan, East Java. Data were collected from respondents through questionnaires and analyzed using Structural Equation Modeling (SEM) to understand the general responses regarding community participation in forest preservation. The results indicate that the human capital of the community, particularly education level and employment, contributes significantly to the success of sustainable forest development. Additionally, social characteristics such as mutual-cooperation and kinship within the community play a vital role in supporting long-term forest management. This community service initiative aims to strengthen both human and social capital to foster a sustainable forest management approach based on local wisdom and community-driven efforts.